Pediatric sacral nerve stimulator explanation due to complications or cure: a survival analysis. Issue 1 (February 2019) - Rensing, A.J.; Szymanski, K.M.; Dunn, S.; King, S.; Cain, M.P.; Whittam, B.M.
Summary: Introduction: Historically, there have been few treatment options for children with severe refractory bladder and bowel dysfunction (BBD). Sacral neuromodulation (SNM) continues to show promising results in this challenging pediatric population with recalcitrant lower urinary tract symptoms. At the authors institution, they have begun offering explantation to those with persistent improvement after >6 months of having device turned off. The authors hypothesized that (1) SNM explantation for cure increases with extended follow-up and (2) those explanted for cure would have improved symptoms and quality of life when compared to those explanted for complication. Materials & methods: The authors retrospectively reviewed all consecutive patients aged <18 years who underwent SNM placements at their institution (2012–2017). They excluded those without the second stage procedure. Reasons for device explantation were categorized as cure (resolution of symptoms with the device turned off for at least 6 months) or a complication (e.g. infection, need for magnetic resonance imaging, or pain). Non-parametric tests and survival analysis were used for analysis to account for differential follow-up time. Of those explanted, surveys were electronically sent to assess BBD severity and overall quality of life. Results: Of 67 children who underwent a first stage procedure, 62 (92.5%) underwent a second stage procedure. 61 met inclusion criteria (68.9% female, 29.5% with previous filum section, median age at implantation 10.3 years). During follow-up (median 2.3 years), 12 patients (19.7%) had the SNM exchanged/revised because of lead fracture/breakage and return of urinary symptoms. To date, 50 patients remain with their SNM implanted, and 11 have been explanted. Adjusting for follow-up time, the risk of explantation was 6.5% at 2 years (2.2% for cure, 4.3% for complications) (Figure 1 ). Explantation increased to 24.5% at 3 years (16.5% for cure, 8.0% for complications) and 40.4% at 4 years (32.4% for cure, 8.0% for complications). Questionnaires were collected on patients after explant (median 2.2 years), with improvement in those explanted for cure compared to complication (Figure 2 ). Discussion: Sacral neuromodulation explantation for cure is a novel concept previously not described in the literature. Limitations of this study include the relatively small numbers and lack of objective data in the cohort that remains with SNM device implanted. Conclusion: Sacral neuromodulation is a safe, viable option for the pediatric patient with refractory bladder dysfunction. Furthermore, SNM explantation for cure is an option with increasing likelihood after 2 years.